Effect of earmold venting on insertion gain - Asha Yathiraj and Roopa Nagarajan (Journal of All India Institute of Speech and Hearing, 1970)
Earmold modifications are recommended to vary the electroacouslic output of hearing aids to suit the individual requirements of the hearing -impaired. Parallel and diagonal venting of earmolds are utilized to boost and I or reduce the gain of the hearing aid at specific frequencies. This study reports the effect ofearmold venting in hearing aid users. Insertion gain measurements were carried out using Madsens IGO 1000. The effect of earmold venting on the gain of the hearing aid at different frequencies were analysed. The study indicated that there was no significant difference between vented and non-vented ear molds.